The founding of Flipz: Living the entrepreneurship dream? - GOH, Kenneth T. (Institutional Knowledge at Singapore Management University, 2019)
Flipz is the pseudonym for a Hong Kong-based mobile classified app for consumer-to-consumer selling and buying of new and second-hand goods. Despite the initial skepticism towards their venture, the founders managed to gain traction with their app and eventually succeeded in raising venture funding at a valuation of US$500 million six years after the company was founded. In January 2016, Lee Ju Ning, the co-founder of Flipz, a peer-to-peer online selling platform for second-hand goods, ponders about the important decisions she has to make in the wake of being confronted with multiple setbacks in her entrepreneurial journey. Eighteen months earlier, Lee and her fellow university classmate, Caden Chan, had returned to Hong Kong, feeling energised after a one-year immersion programme in Silicon Valley. Shortly after, Lee and Chan spotted a business opportunity and brought their idea of simplifying the cumbersome process of online listing and selling second-hand items to a hackathon competition. They eventually emerged the champion and with the winner’s prize, Flipz was founded, despite disapproval from Lee’s parents. The entrepreneurship journey was indeed not as smooth as expected, and there were many lessons to be learnt from the school of hard knocks. Successive challenges began to dampen the initial high spirits - funding rejections, technical difficulties during product development, and dwindling user downloads following a successful launch. Lee faces a common dilemma encountered by many budding tech entrepreneurs – whether to channel the remaining limited funds to marketing or product development. She also begins to cast doubts on the future: Should she hang on to the start-up or call it quits?